2006
DOI: 10.1016/s0210-4806(06)73414-3
|View full text |Cite
|
Sign up to set email alerts
|

Biopsia prostática ecodirigida: comparación de dos métodos anestésicos

Abstract: The use of bilateral periprosthetic block with mepivacaine is a very effective and useful technique, well tolerated by the patient, which almost completely abolishes the pain and discomfort associated with the prostate biopsy procedure. And also allows increase the number of cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[ 13 , 14 ] PNB was an effective way of anesthesia for prostate puncture, [ 15 ] which could directly infiltrate the neurovascular bundle. [ 16 ] Conde et al [ 17 ] found that bilateral PNB had better anesthetic effect than oral morphine. A meta-analysis conducted by Hergan, [ 18 ] which included 14 studies, revealed that PNB was better than local anesthesia or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] PNB was an effective way of anesthesia for prostate puncture, [ 15 ] which could directly infiltrate the neurovascular bundle. [ 16 ] Conde et al [ 17 ] found that bilateral PNB had better anesthetic effect than oral morphine. A meta-analysis conducted by Hergan, [ 18 ] which included 14 studies, revealed that PNB was better than local anesthesia or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Conde et al [7] in 2006 found that bilateral periprostatic nerve block is better for analgesia than oral morphine. Over the years, it has been established by various authors that periprostatic nerve block is very effective for TRUS-guided prostate biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Nash et al [11] were the first to introduce PNB, and found that it can relieve the pain during transrectal ultrasound (TRUS) -guided prostate biopsy. Conde et al [12] found that the anesthesia effect of PNB was superior to oral morphine. Hergan et al [13] conducted a meta analysis of fourteen trials and found that PNB had better anesthesia effect than that of local anesthesia or placebo.…”
Section: Introductionmentioning
confidence: 99%